Rhynchorhina mauritaniensis, a new genus and species of wedgefish from the eastern central Atlantic (Elasmobranchii: Batoidea: Rhinidae) - Séret, Bernard; Naylor, Gavin J.p. (Zootaxa, 2016)
A new wedgefish, Rhynchorhina mauritaniensis gen. et sp. nov., is described from three specimens collected in the shallow waters of the shoal “Banc d’Arguin”, off Mauritania (Eastern Central Atlantic). The new genus is mainly distinguished from its close relatives, members of the genus Rhynchobatus, by its snout shape, more broadly rounded like that of the shark-ray Rhina ancylostoma, instead of being typically wedge-shaped as in Rhynchobatus species. The new species resembles the common West African wedgefish, Rhynchobatus lubberti, in having a similar colour pattern, but differs in snout shape. The new genus is supported as genetically distinct by comparative analysis of the mitochondrial NADH2 gene.